2009
DOI: 10.1038/jes.2009.58
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian hierarchical modeling of cardiac response to particulate matter exposure

Abstract: Studies have linked increased levels of particulate air pollution to decreased autonomic control, as measured by heart rate variability (HRV), particularly in susceptible populations such as the elderly. In this study, we use data obtained from the 1998 USEPA epidemiology-exposure longitudinal panel study of elderly adults in a Baltimore retirement home to examine the relationship between HRV and PM 2.5 personal exposure. We consider PM 2.5 personal exposure in the aggregate and personal exposure to the compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…The latent variables correspond to what is “ common ” among the parameters measured and do not preclude in part different biological processes. Several studies have used SEMs that assessed source-specific health effects of air pollution [5,6] and in health effects of methyl mercury [7] and lead on neurodevelopment [8]. Notably, in models with 3 or more surrogates of the latent exposure, SEMs reduce the attenuation due to measurement error which is an ongoing concern in air pollution studies [9].…”
Section: Introductionmentioning
confidence: 99%
“…The latent variables correspond to what is “ common ” among the parameters measured and do not preclude in part different biological processes. Several studies have used SEMs that assessed source-specific health effects of air pollution [5,6] and in health effects of methyl mercury [7] and lead on neurodevelopment [8]. Notably, in models with 3 or more surrogates of the latent exposure, SEMs reduce the attenuation due to measurement error which is an ongoing concern in air pollution studies [9].…”
Section: Introductionmentioning
confidence: 99%
“…Health effects are believed to lag exposure, and the moving average is a tool used to estimate the cumulative impact of pollutant concentrations and is more consistent with actual exposure than the block averages typically used in compliance monitoring (Amancio et al, 2012;Kloog et al, 2012;Mar et al, 2005;Mcbride et al, 2011). The time span most relevant to human exposure in clinical trials is 5-10 min, as only one study reviewed reported respiratory effects under 5 min (Horstman et al, 1988).…”
Section: Air Monitoring In Relation To Health Criteriamentioning
confidence: 99%
“…Epidemiological studies show different associations between adverse health effects and particles with aerodynamic diameters of less than 2.5 μm (PM 2.5 ) and less than 10 μm (PM 10 ) (Barmpadimos et al, 2011;Mcbride et al, 2011). The sources of PM 2.5 and PM 10 are different, and include a wide range of natural phenomena and human activities.…”
Section: Introductionmentioning
confidence: 99%